An investigation of the refusal speech act of Turkish learners of English - Gungormezler, Tugce (Kansas State University, 2016)
This study investigates and compares politeness strategies of Turkish learners of English (TLE) and American English speakers (AE) when they produce the speech act of refusal in English. A total of 24 participants took part in this study and each of them completed a background survey, an open role play and a semi-structured interview. The role-play asked all of the participants to refuse a party invitation offered by a classmate/colleague and was audio-recorded. The refusal interactions were coded according to the classification proposed by Beebe et al. (1990), and the sequence of the refusal interactions (i.e., head act, pre- and post-refusals) was also examined. The results showed that providing excuse/reason/explanation was the most preferred strategy by both groups overall, but closer examination of the strategy revealed that the TLE group was more specific in their explanations compared to the AE group. In addition, when the conductor of the role play insisted on the invitation, the AE group continued to refuse without giving specific reasons, whereas the TLE group chose to provide elaborate reasons upon insistence. During the interview session after the role play, the TLE group commented on cultural factors that influenced their choice of refusal strategies. Based on the findings, this study also proposed implications of the teaching of pragmatics in the English as a second language (ESL) context.
Keywords: Interlanguage pragmatics; Speech act of refusal; Culture; Turkish learners of English; American English speakers